The system of equations
4
a
4
+
3
6
a
2
b
2
+
9
b
4
=
2
0
a
2
+
3
0
b
2
−
1
2
a
3
b
+
3
a
b
3
=
5
a
b
has
n
nonnegative (meaning both
a
and
b
are nonnegative) real solutions. Let these solutions be
(
a
1
,
b
1
)
,
(
a
2
,
b
2
)
,
⋯
(
a
n
,
b
n
)
. The value of the sum
i
=
1
∑
n
a
i
+
b
i
can be expressed in the form
d
a
+
b
c
where
g
cd
(
a
,
b
,
d
)
=
1
and
c
is squarefree. Find
a
+
b
+
c
+
d
.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Multiply the second equation by 4 6 , add it to the first, then factor to get ( a 2 + b 3 ) 4 = 1 0 ( a 2 + b 3 ) 2 − 1 . Letting x = a 2 + b 3 and rearranging gives x 4 − 1 0 x 2 + 1 = 0 Which can be solved as a quadratic in x 2 after which x can be computed as ± 2 ± 3 , after which the solutions are easy to find.
Missed the fact that g cd ( a , b , d ) = 1 :( And of course my immediate reaction - reveal solution :D I'm curious what the fraction is as I am bad at manipulating them.
a b ( 2 a 2 + 3 b 2 ) = 5 a b a b = 0 o r 2 a 2 + 3 b 2 = 5 ( 2 a 2 + 3 b 2 ) 2 + 2 4 a 2 b 2 = 1 0 ( 2 a 2 + 3 b 2 ) − 1 = 5 0 − 1 = 4 9 2 5 + 2 4 a 2 b 2 = 4 9 2 4 a 2 b 2 = 2 4 a 2 b 2 = 1 2 a 2 + 3 b 2 = 5 2 a 2 + 3 ( a 2 1 ) = 5 2 a 4 + 3 = 5 a 2 a 2 = 2 3 , b 2 = 3 2 a b = 0 < = > a = 0 , b = 0 a = 0 , 9 b 4 = 3 0 b 2 − 1 9 b 4 − 3 0 b 2 + 1 = 0 b 2 = 9 + − 2 1 6 + 1 5 b 1 = 3 + 2 1 6 + 1 5 b 2 = 3 − 2 1 6 + 1 5 b 1 + b 2 = 3 1 ( 2 1 6 + 1 5 + − 2 1 6 + 1 5 ) = − 2 1 6 + 1 5 1 + + 2 1 6 + 1 5 1 = − 6 6 + 1 5 1 + 6 6 + 1 5 1 b = 0 4 a 4 − 2 0 a 2 + 1 = 0 a 2 = 4 + − 9 6 + 1 0 a 1 = 2 + 9 6 + 1 0 a 2 = 2 − 9 6 + 1 0 S = 2 + 6 5 + − 6 6 + 1 5 1 + + 6 6 + 1 5 1 + + 4 6 + 1 0 1 + − 4 6 + 1 0 1 = 2 + 6 5 + 3 ∗ ( 3 − 2 ) 1 + 3 ∗ ( 3 + 2 ) 1 + 2 ∗ ( 3 + 2 ) 1 + 2 ∗ ( 3 − 2 ) 1 = 6 2 6 + 5 + 2 ( 3 + 2 ) + 2 ( 3 − 2 ) + 3 ( 3 − 2 ) + 3 ( 3 + 2 ) = 6 2 6 + 6 + ( 3 + 2 ) 2 = 6 2 6 + 6 + 5 + 2 6 = 6 1 1 + 4 6 = 6 6 ( 1 1 + 4 6 ) = 6 2 4 + 1 1 6 a + b + c + d = 4 7
From the second equation, I found that a =0 or b = 0 or 2.a^2+3.b^2 = 5.
If a = 0, from the first equation, I have 9.b^4-30.b^2+1=0.
If b = 0, from the first equation, I have 4.a^4-20.a^2+1=0.
If 2.a^2+3.b^2=5, I have a=b=1 or a= \frac{3}{2} .b .
Problem Loading...
Note Loading...
Set Loading...
Factor the second equation:
a b ( 2 a 2 + 3 b 2 − 5 ) = 0
First we have a = 0 . Substitute that in the first equation to obtain:
9 b 4 − 3 0 b 2 + 1 = 0
That equation has two positive roots: b = 3 3 ± 6
Now with b = 0 do the same:
4 a 4 − 2 0 a 2 + 1 = 0
That equation has two positive roots: a = 2 6 ± 2
Finally, do the same with 2 a 2 + 3 b 2 = 5 . Rearrange the first equation:
( 2 a 2 + 3 b 2 ) 2 + 2 4 a 2 b 2 = 1 0 ( 2 a 2 + 3 b 2 ) − 1
5 2 + 2 4 a 2 b 2 = 1 0 ( 5 ) − 1
a 2 b 2 = 1 ⟹ a 2 = b 2 1
Substitute that in 2 a 2 + 3 b 2 = 5 :
b 2 2 + 3 b 2 = 5 ⟹ 3 b 4 − 5 b 2 + 2 = 0
That equation has two positive roots: b = 1 and b = 3 6 . For a we get, respectively: a = 1 and a = 2 6 .
Finally, our pairs are: ( a , b ) = ( 0 , 3 3 + 6 ) , ( 0 , 3 3 − 6 ) , ( 2 6 + 2 , 0 ) , ( 2 6 − 2 , 0 ) , ( 1 , 1 ) , ( 2 6 , 3 6 )
Sum everything and you get: 6 2 4 + 1 1 6 . So, the final answer is 2 4 + 1 1 + 6 + 6 = 4 7 .